2005
DOI: 10.1248/bpb.28.1892
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition, Antibacterial and Antioxidant Activity of the Oil and Various Extracts of Ziziphora clinopodioides subsp. rigida (BOISS.) RECH. f. from Iran

Abstract: The chemical composition of the essential oil obtained from the aerial parts of Z. clinopodioides subsp. rigida (BOISS.) RECH. f. was analysed by GC and GC-MS. Thirty-one constituents accounting to 99.5% of the total oil were identified. Oxygenated monoterpenes (93.3%) were the predominant portion of the oil with pulegone (45.8%), piperitenone (17.4%), p-menth-3-en-8-ol (12.5%) and thymol (8.0%) as the main constituents. Antibacterial activity of the oil and its two main compounds and various extracts of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 16 publications
5
118
3
Order By: Relevance
“…These results are compatible with the results reported by Salehi et al (2005), who reported that a methanol extract of this plant exhibited antibacterial activity against B. subtilis, S. aureus, and E. coli. However, acetone extract of Iranian Z. clinopodioides subsp.…”
Section: Antimicrobial Activities Of Extractssupporting
confidence: 93%
See 4 more Smart Citations
“…These results are compatible with the results reported by Salehi et al (2005), who reported that a methanol extract of this plant exhibited antibacterial activity against B. subtilis, S. aureus, and E. coli. However, acetone extract of Iranian Z. clinopodioides subsp.…”
Section: Antimicrobial Activities Of Extractssupporting
confidence: 93%
“…However, acetone extract of Iranian Z. clinopodioides subsp. rigida has not shown any antibacterial activity (Salehi et al, 2005). Convensely, in the current study, the acetone extract of Turkish Z. clinopodioides showed a remarkable antibacterial activity.…”
Section: Antimicrobial Activities Of Extractscontrasting
confidence: 48%
See 3 more Smart Citations